Developing Reading Worksheet for Tenth Grade Students of SMA Negeri 4 Palopo - Anwar, Lestari; Furwana, Dewi; Iksan, Muhammad (Faculty of Education and Teacher Training of IAIN Palopo, 2020)
This research about Developing Students' Reading Worksheet of tenth grade at SMA Negeri 4 Palopo, the researcher formulated the research question as follow: what kind of Reading Worksheet are suitable for tenth students'. The objective of this research is to create and develop reading worksheets for tenth-grade students' by using the Addie design model. In this research and development from the Addie model, this consists of Analyzing, Designing, Implementation, and evaluating. There are 14 students and two experts' validation. The instrument of the data collection is a questioner. The result of the research shows that the researcher develops and make a product based on the students' need. And the development of this product is also carried out based on the syllabus and curriculum that apply in the school itself. Based on the worksheet, have a development already appropriate necessity and lack of the students, and with the development worksheet would students' reading ability.